2009
DOI: 10.1002/mus.21163
|View full text |Cite
|
Sign up to set email alerts
|

Sensory loss in multifocal motor neuropathy: A clinical and electrophysiological study

Abstract: Some patients fulfilling the criteria for the diagnosis of multifocal motor neuropathy with conduction block (MMN-CB) at the onset of disease may subsequently develop a sensory loss associated with electrophysiological sensory abnormalities. The latter could represent an overlap between MMN-CB and multifocal acquired demyelinating sensory and motor (MADSAM) neuropathy. The objective was to specify the features of MMN-CB with sensory loss (MMN-CB-Se). Five patients in a series of 11 consecutive patients who ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
1
16
0
8
Order By: Relevance
“…This study confirms that a decrease in SNAP amplitude may occur during the course of the disease of some MMNCB patients [8,11]. Typically in this neuropathy, clinical and electrophysiological involvements are restricted to motor nerves, but previous anatomic-pathological studies have demonstrated mild axonal and demyelinating abnormalities in the sensory nerve biopsies of patients with MMNCB [2,3,7,13,15].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This study confirms that a decrease in SNAP amplitude may occur during the course of the disease of some MMNCB patients [8,11]. Typically in this neuropathy, clinical and electrophysiological involvements are restricted to motor nerves, but previous anatomic-pathological studies have demonstrated mild axonal and demyelinating abnormalities in the sensory nerve biopsies of patients with MMNCB [2,3,7,13,15].…”
Section: Discussionsupporting
confidence: 75%
“…Two electrophysiological studies have recently reported a decrease in SNAP amplitude during the follow-up of 13 patients out of 21 MMNCB [11] and of 5 patients out of 11 MMNCB [8]. Difference in the clinical presentation between MMNCB patients with normal or decreased SNAP amplitude has not been reported in these studies, but parameters such as number of affected regions, ONLS incapacity scale and minimal dosage of IVIg to maintain clinical improvement were not evaluated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, patients showing a reduction in Sural nerve action potential (SNAP) amplitude presented with a more severe disease and more prominent axonal loss 44. Some authors suggest that a subgroup of MMN patients may subsequently develop electrophysiological sensory abnormalities and this entity may represent an overlap between classical MMN and multifocal acquired demyelinating sensory and motor neuropathy 45. Further studies with larger patient numbers should evaluate the extent to which MMN patients are affected in CCM and whether this impairment is associated with particular clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Making the correct differential diagnosis is of more than academic interest because some patients with Lewis-Sumner syndrome respond to steroids, which are ineffective or even harmful in MMN patients (see below) [121,122]. Whether it is really of clinical relevance to further separate pure MMN from MMN with sensory loss and MADSAM neuropathy clearly needs further evaluation [123]. Finally, acquired or hereditary entrapment neuropathies, e.g.…”
Section: Diagnostic Criteria and Differential Diagnosismentioning
confidence: 99%